Not all subsidies are equal: measuring preferences for electric vehicle financial incentives. (1st August 2022) - Roberson, Laura; Helveston, John Paul
Abstract: Financial incentives, such as purchase subsidies, have been found to increase plug-in electric vehicle (PEV) adoption, but how these incentives are designed can impact their effectiveness as well as how equitably they are distributed. Using a national conjoint survey ( N = 2170 respondents), we quantify how U.S. vehicle buyers value different features of PEV financial incentives. Participants overwhelmingly prefer immediate rebates, on average valuing them by $580, $1450, and $2630 more than sales tax exemptions, tax credits, or tax deductions, respectively. These effects are significantly larger for lower-income households, used vehicle buyers, and buyers with lower budgets. We estimate that on average $2 billion could have been saved if the federal subsidy available between 2011 and 2019 were delivered as an immediate rebate instead of a tax credit, or $1440 per PEV sold. Our results suggest that structuring incentives as immediate rebates would deliver a greater value to customers and would be more equitably distributed compared to the current tax credit scheme.